Reconstruction of the Anterior Cruciate Ligament Using Ruler-Assisted Positioning of the Femoral Tunnel Relative to the Posterior Apex of the Deep Cartilage: A Single-Center Case Series - Dong, Yan; Tang, Jiaguang; Cui, Peng; Shen, Songpo; Wang, Guodong; Li, Jian; Kong, Xiaochuan; Hong, Gang; Yuan, Shuo; Zang, Lei (The Journal of Knee Surgery, 2021)
The techniques available to locate the femoral tunnel during anterior cruciate ligament (ACL) reconstruction have notable limitations. To evaluate whether the femoral tunnel center could be located intraoperatively with a ruler, using the posterior apex of the deep cartilage (ADC) as a landmark. This retrospective case series included consecutive patients with ACL rupture who underwent arthroscopic single-bundle ACL reconstruction at the Department of Orthopedics, Beijing Tongren Hospital between January 2014 and May 2018. During surgery, the ADC of the femoral lateral condyle was used as a landmark to locate the femoral tunnel center with a ruler. Three-dimensional computed tomography (CT) was performed within 3 days after surgery to measure the femoral tunnel position by the quadrant method. Arthroscopy was performed 1 year after surgery to evaluate the intra-articular conditions. Lysholm and International Knee Documentation Committee (IKDC) scores were determined before and 1 year after surgery. The final analysis included 82 knees of 82 patients (age = 31.7 ± 6.1 years; 70 males). The femoral tunnel center was 26 ± 1.5% in the deep-shallow (x-axis) direction and 31 ± 3.1% in the high-low (y-axis) direction, close to the “ideal” values of 27 and 34%. Lysholm score increased significantly from 38.5 (33.5–47) before surgery to 89 (86–92) at 1 year after surgery (p < 0.001). IKDC score increased significantly from 42.5 (37–47) before surgery to 87 (83.75–90) after surgery (p < 0.001). Using the ADC as a landmark, the femoral tunnel position can be accurately selected using a ruler.
Keywords: anterior cruciate ligament; anatomic reconstruction; ruler; bone tunnel; secondary exploration